The health awareness among students of Bachelor in Office System Management in UiTM Perak / Ahmad Aizuddin Ahmad Taufik, Ahmad Syazrul Ahmad Ruslan and Marshiela Mahzair - Ahmad Taufik, Ahmad Aizuddin; Ahmad Ruslan, Ahmad Syazrul; Mahzair, Marshiela (2012)
The purpose of this study is to analyze the factors that contribute to the increasing number of unhealthy students Bachelor in Office System Management, Faculty of Business Management, UiTM Perak. The objectives of this study were to measure student lifestyle, environment and stress that affect student health.The methodology approach on this research paper is based on student awareness on their health. This study is limited to I 00 students of Bachelor in Office System Management UiTM Perak from semester 3 until semester 6. One hundred (100) questionnaires were distributed to all respondents and all of them are returned. These findings were analyzed using SPSS 20.The finding of this study is to identify the students' demographic profile, lifestyle, environment, and stress that affect the health of the students. These factors are very significantly influence to determine the health awareness.The last section of this study discussed about the conclusion and recommendation in order to maintain a healthy life. Students need to be extra concerns about their health in order to maintain a healthy balance lifestyle.